1982
DOI: 10.1111/j.1744-7348.1982.tb01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of streak virus‐resistant maize populations through improved challenge and selection methods

Abstract: SUMMARY Tolerance to maize streak virus (MSV) was found and rapidly incorporated into high yielding maize populations for the tropics. Methods were developed for vector propagation and rapid accurate screening of many accessions for virus tolerance in large screenhouses. Tolerance was found in only two accessions and at low frequencies. Further refinements enabled field evaluation for virus tolerance to be combined with high agronomic performance. The tolerance found is simply inherited and was fixed rapidly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 8 publications
1
40
0
Order By: Relevance
“…The plants were inoculated at the 3-leaf stage in the field by attaching a small plastic vial with three viruliferous leafhoppers onto distal portions of the youngest leaf. A rating scale of 1 (no symptoms) to 5 (severe streaking with chlorosis) based on the protocol described by Soto et al (1982) was used. MSV severity was rated on plot basis using the 1-5 scale with half points as follows: 1= no symptom on leaves; 1.5= very few streaks on leaves; 2= light streak on old leaves, gradually decreasing on young leaves; 2.5= light streaking on old and young leaves; 3= moderate streaks on old and young leaves; 3.5= moderate streaks on old and young leaves and slight stunting; 4= severe streaking on 60% of leaf area, plants stunted; 4.5= severe streaking on 75% of leaf area, plants severely stunted and 5= severe streaking on 75% or more of the leaf area, plants severely stunted, dying or dead.…”
Section: Msv Disease Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants were inoculated at the 3-leaf stage in the field by attaching a small plastic vial with three viruliferous leafhoppers onto distal portions of the youngest leaf. A rating scale of 1 (no symptoms) to 5 (severe streaking with chlorosis) based on the protocol described by Soto et al (1982) was used. MSV severity was rated on plot basis using the 1-5 scale with half points as follows: 1= no symptom on leaves; 1.5= very few streaks on leaves; 2= light streak on old leaves, gradually decreasing on young leaves; 2.5= light streaking on old and young leaves; 3= moderate streaks on old and young leaves; 3.5= moderate streaks on old and young leaves and slight stunting; 4= severe streaking on 60% of leaf area, plants stunted; 4.5= severe streaking on 75% of leaf area, plants severely stunted and 5= severe streaking on 75% or more of the leaf area, plants severely stunted, dying or dead.…”
Section: Msv Disease Screeningmentioning
confidence: 99%
“…Many studies suggest that the obvious strategy to reduce maize yield losses caused by MSV would be to develop MSV resistant and/or tolerant cultivars (van Rensburg, 1981;Soto et al, 1982;Shoyinka, 1988). The development of maize germplasm that is resistant to MSV has therefore been the goal of several breeding programs in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Maize streak virus (MSV) occurs naturally in many plants of the Gramineae throughout Africa (Storey & McClean, 1930;Rose, 1978), Mauritius (Ricaud & F61ix, 1978), R6union (Soto et al, 1982), Vanuatu (Dollet et al, 1986) and possibly India (Seth et al, 1972). The host range of MSV includes maize, other cereals and sugarcane making it an economically important pathogen (Damsteegt, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The MSV resistance in inbred TZ-Y was considered to be simply inherited (Soto et al, 1982), but Kim et al (1989) reported that resistance in inbred IB32 (Ibadan 32 -developed from TZ-Y) was quantitatively inherited through additive action of up to several genes. More recent studies of genetic control of MSV resistance in population CVR3-C3 have shown that multiple genetic systems for resistance to MSV may indeed exist (Rodier et al, 1995).…”
Section: Improving Host Resistancementioning
confidence: 99%